(untitled) (Research, Society and Development, 2020)
Currently, it has been verified, both in academic research and in political-institutional discussions, proposals on how to fight criminal organizations more effectively, since organized crime is increasingly closely associated with the action of the State. This paper aims to demonstrate which are the endogenous criminal organizations in the State of Pará and how they act, based on the analysis of criminal actions filed by the Special Action Group to Combat Organized Crime of the Public Ministry (State Prosecution) of the State of Pará. Using the technique of descriptive statistics with a quantitative focus of the data, the present research was primarily based on a documentary analysis, from a census of criminal actions filed in the period from 2014 to 2018, in the State of Pará. The results point to the existence of 4 (four) types of criminal organizations with different forms of action, practicing criminal conduct such as passive corruption, fraudulent misrepresentation, insertion of false data in information systems, money laundering, among others, in several municipalities in the State of Pará, as well as in other states, causing serious damage to the community. Thus, it can be concluded that there are criminal groups in the State of Pará that rely on the direct participation of public agents, and even those formed exclusively by public servants, contributing to the success of the criminal enterprise.